Running impact forces: from half a leg to holistic understanding - comment on Nigg et al. - Kenneth P. Clark; Andrew B. Udofa; Laurence J. Ryan; Peter G. Weyand (Bern Open Publishing, 2018)
Running impact forces have immediate relevance for the muscle tuning paradigm proposed here and broader relevance for overuse injuries, shoe design and running performance. Here, we consider their mechanical basis. Several studies demonstrate that the vertical ground reaction force-time (vGRFT) impulse, from touchdown to toe-off, corresponds to the instantaneous accelerations of the body's entire mass (Mb) divided into two or more portions. The simplest, a two-mass partitioning of the body (lower-limb, M1=0.08•Mb; remaining mass, M2=0.92•Mb) can account for the full vGRFT waveform under virtually all constant-speed, level-running conditions. Model validation data indicate that: 1) the non-contacting mass, M2, often accounts for one-third or more of the early "impact" portion of the vGRFT, and 2) extracting a valid impact impulse from measured force waveforms requires only lower-limb motion data and the fixed body mass fraction of 0.08 for M1.